Sumoylation of the Carboxy-Terminal of Human Cytomegalovirus DNA Polymerase Processivity Factor UL44 Attenuates Viral DNA Replication - Chen, Jun; Li, Guanlie; He, Haiqing; Li, Xin; Niu, Wenjing; Cao, Di; Shen, Ao (Frontiers in Microbiology, 2021)
Controlled regulation of genomic DNA synthesis is a universally conserved process for all herpesviruses, including human cytomegalovirus (HCMV), and plays a key role in viral pathogenesis, such as persistent infections. HCMV DNA polymerase processivity factor UL44 plays an essential role in viral DNA replication. To better understand the biology of UL44, we performed a yeast two-hybrid screen for host proteins that could interact with UL44. The most frequently isolated result was the SUMO-conjugating enzyme UBC9, a protein involved in the sumoylation pathway. The UBC9-UL44 interaction was confirmed by in vitro His-tag pull-down and in vivo co-immunoprecipitation assays. Using deletion mutants of UL44, we mapped two small regions of UL44, aa 11-16 and 260-269, which might be critical for the interaction with UBC9. We then demonstrated that UL44 was a target for sumoylation by in vitro and in vivo sumoylation assays, as well as in HCMV-infected cells. We further confirmed that 410lysine located within a ψKxE consensus motif on UL44 carboxy-terminal was the major sumoylation site of UL44. Interestingly, although 410lysine had no effects on subcellular localization or protein stability of UL44, the removal of 410lysine sumoylation site enhanced both viral DNA synthesis in transfection-replication assays and viral progeny production in infected cells for HCMV, suggesting sumoylation can attenuate HCMV replication through targeting UL44. Our results suggest that sumoylation plays a key role in regulating UL44 functions and viral replication, and reveal the crucial role of the carboxy-terminal of UL44, for which little function has been known before.